Optimization of Information Volume in a Partially Decentralized Decision Support System - Савченко, М. М.; Циганок, В. В. (Інститут проблем реєстрації інформації НАН України, 2023)
Decision support systems can be partially decentralized using blockchain technology like almost any other systems where it makes sense. Partial decentralization, or, in other words, moving a part of the system responsibilities onto existing public decentralized data platforms such as Ethereum provides new useful properties in the area of security, verification, and makes some information publicly auditable. Particular systems such as decision support systems may benefit from this, as they now have a practical way to verify the data input with no way to change it retroactively. However, decentralization increases the nominal cost of maintaining the system, as part of the data will now be stored in a decentralized public registry. Compared to running a classical computer system where institutions or researchers can bring their own hardware to run things on, there's always a non-zero extra cost associated with using the public decentralized data platform. This study reviews and offers approaches that can reduce the cost of storing information in decentralized data registries by combining methods of data minimization together with the specific system architecture design. Provided numerical examples of the method of storing information in the decentralized Ethereum registry, which allows reducing the cost of data recorded in the decentralized registry by more than 80 % by changing the way how transactions are sent to the decentralized network. Substantiated the feasibility of transferring the proposed data storage methods to other Ethereum-compatible (EVM) decentralized data platforms for further reduction of data storage costs in decentralized registries. Reviewed the real cost example of a system running on top of popular, EVM-compatible decentralized data platforms at the specific moment in time, where demonstrated that Ethereum is the most expensive choice among other decentralized networks. Tabl.: 1. Fig.: 6. Refs: 12 titles.